Hak Cipta Dalam Industri Musik: Analisis Terhadap Perlindungan Dan Pembajakan - Kartika Utami Lubis; Romi Faslah (GLOBAL SCIENTS PUBLISHER, 2025)
This research discusses the legal protection of copyright in the music industry and the challenges faced due to rampant piracy, especially in the digital era. Copyright is an important aspect in maintaining the economic and moral rights of songwriters and musicians. Despite the existence of national regulations such as Law No. 28/2014 on Copyright and ratification of international treaties, copyright infringement still occurs in various forms, ranging from illegal duplication, unauthorized distribution, to the use of songs in performances without royalties. This article analyzes the impact of piracy on music industry revenue and creator motivation, and highlights the role of technology-both as a cause and a solution through systems such as Digital Rights Management (DRM). In addition, the study evaluates the efforts of governments, industry players, and collective organizations in enforcing the law and raising public awareness of the importance of respecting copyright. The results show that strong law enforcement, cross-sector cooperation, and public education are strategic steps in reducing piracy and strengthening a sustainable music industry ecosystem.